Proteomics Analysis Reveals Bacterial Antibiotics Resistance Mechanism Mediated by ahslyA Against Enoxacin in Aeromonas hydrophila - Li, Zhen; Zhang, Lishan; Song, Qingli; Wang, Guibin; Yang, Wenxiao; Tang, Huamei; Srinivasan, Ramanathan; Lin, Ling; Lin, Xiangmin (Frontiers in Microbiology, 2021)
Although bacterial antibiotic resistance is a serious global problem, the underlying regulatory mechanisms are largely elusive. Here, we report on the involvement of the multiple antibiotic resistance family transcriptional regulator in Aeromonas hydrophila, AhSlyA, in quinolone resistance, especially enoxacin (ENX). A label-free quantitative proteomics method was utilized to compare the protein profiles of the ahslyA knockout and wild-type A. hydrophila strains under ENX stress. Bioinformatics analysis showed that the deletion of ahslyA triggered antibiotics resistance genes in the bacteria that reduce the pressure from ENX such that the SOS repair system didn’t be aroused. Moreover, ahslyA directly or indirectly induced at least 11 transcriptional regulators, indicating a complicated regulatory network under ENX stress. We also deleted six selected genes in A. hydrophila that altered in proteomics data in order to evaluate their roles in ENX stress. Our results showed that AHA_0655, narQ, AHA_3721, AHA_2114, and AHA_1239, all regulated by ahslyA, may be involved in ENX resistance. Overall, our data demonstrated the important role of ahslyA in ENX resistance and provided novel insights into the effects of transcriptional regulation on antibiotic resistance in bacteria.